Isolasi dan mikroenkapsulasi vitamin E dari crude palm oil sebagai sumber antioksidan bahan pangan Isolation and microencapsulation of vitamin E from crude palm oil as source of food antioxidant - Irma KRESNAWATY; Asmini BUDIANI; . TRI-PANJI; . SUHARYANTO (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2012)
AbstractIn order to increase value added and to support downstream industry of palm oil, minor components of the oil such as β-carotene and vitamin E should be utilized. Vitamin E is a high value vitamin that could be used as material for pharmaceutical and neutraceutical products. Technological constraints encountered in the utilization of vitamin E from CPO are lack of optimal extraction and purification method as well as the way to stabilize of the product. The research was conducted to find optimal extraction and purification method of vitamin E from CPO and microencapsulation method of vitamin E as pharmaceutical and neutraceutical product. The research showed that vitamin E could be recovered from CPO by several steps process including saponification using NaOH, separation of unsaponificated solution, followed by dissolution using 2-propanol in hexane and extraction using methanol. Raw extract of vitamin E was then purified by coloumn chromatography with stationary phase of silica gel and mobile phase (eluent) of petroleum benzene/ diethyl ether/acetic acid 70 : 30 : 0,2. Purified vitamin E could be collected as fraction 4-8. Vitamin E obtained had similar antioxidant activity as in pure vitamin E (Sigma) and vitamin C. Microencapsulation method could be conducted using arabic gum as coating material followed by spray drying and resulted IC50-DPPH value 132.55 ppm which considered middle activity category.AbstrakUntuk meningkatkan nilai tambah dan mengem-bangkan industri hilir minyak kelapa sawit (CPO), komponen minor minyak tersebut seperti vitamin E dan β-karoten perlu dimanfaatkan. Vitamin E merupakan produk bernilai ekonomis tinggi sebagai bahan farmaseutikal dan neutrasetikal. Kendala yang dihadapi dalam pemanfaatan vitamin E dari CPO, yaitu belum tersedianya teknik ekstraksi dan purifikasi yang optimal dan cara memper-tahankan stabilitas vitamin E. Penelitian ini bertujuan untuk memperoleh teknik ekstraksi dan purifikasi vitamin E dari CPO dan teknik mikroenkapsulasi vitamin E sebagai bahan farmaseutikal dan neutrasetikal. Hasil penelitian menunjukkan bahwa vitamin E dapat diproduksi dengan beberapa tahapan yakni saponifikasi dengan NaOH, pemisahan lapisan pekat tak tersabunkan, pelarutan dengan2-propanol dalam heksana, ekstraksi dengan metanol dan pelarutan ekstrak dengan 2-propanol dalam heksana. Ekstrak kasar vitamin E dimurnikan dengan kromatografi kolom dengan fasa diam silika gel dan fasa gerak petroleum benzen/dietil eter/asam asetat = 70 : 30 : 0,2. Vitamin E dapat dimurnikan pada fraksi ke-4 sampai dengan ke-8. Aktivitas antioksidan vitamin E hasil ekstraksi tersebut setara dengan vitamin E murni (Sigma). Teknik mikroenkapsulasi vitamin E hasil ekstraksi dari CPO dapat dilakukan dengan penyalut gum arab dan pengeringan dengan spray dryer yang menghasilkan anti-oksidan dengan aktivitas IC50 DPPH = 132,55 ppm yang termasuk kategori beraktivitas sedang.